The biggest problem in post-communist transition: The privatization of large enterprises - Anders Åslund (Center for Social and Economic Research (CASE), 2021)
Thirty years after the collapse of the Soviet Union, it is rather clear what transition policies have worked. Almost all the post-communist countries have become market economies and have achieved macroeconomic stability. Privatization was economically necessary, and its economic outcomes have been very positive. Alas, politically, these successes have often been unsustainable because of strong popular sentiments against the private ownership of big enterprises. Substantial renationalization has occurred. What went wrong? How could privatization be done better, or be defended? What should be done to defend private enterprise in the future? This paper argues that the nature of privatization is far less important than the establishment of good rule of law so that private property rights can be defended.
Keywords: P20; P26; P30; P31; K00; K42; 330; Eastern Europe; former Soviet Union; post-communist transformation; market economy; privatization